2010
DOI: 10.1086/597529
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Induces Oxidative Damage to RNA and DNA in a Sulfide‐Tolerant Marine Invertebrate

Abstract: Hydrogen sulfide acts as an environmental toxin across a range of concentrations and as a cellular signaling molecule at very low concentrations. Despite its toxicity, many animals, including the mudflat polychaete Glycera dibranchiata, are periodically or continuously exposed to sulfide in their environment. We tested the hypothesis that a broad range of ecologically relevant sulfide concentrations induces oxidative stress and oxidative damage to RNA and DNA in G. dibranchiata. Coelomocytes exposed in vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 65 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…Death of U. unicinctus juveniles in the 200 U group might be due to the presence of sulphides in the sediments. Excessive sulphides in the sediments are toxic to cultured organisms and can lead to apoptosis and oxidative damage (Joyner‐Matos, Predmore, Stein, Leeuvenburgh & Julian, 2010; Yang, Sun, & Wang, 2004). Although U. unicinctus is more resistant to sulphides than other benthic invertebrates (Zhang & Li 2011), the 200 U group was exposed to extremely high sulphide levels when compared to other stocking densities (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Death of U. unicinctus juveniles in the 200 U group might be due to the presence of sulphides in the sediments. Excessive sulphides in the sediments are toxic to cultured organisms and can lead to apoptosis and oxidative damage (Joyner‐Matos, Predmore, Stein, Leeuvenburgh & Julian, 2010; Yang, Sun, & Wang, 2004). Although U. unicinctus is more resistant to sulphides than other benthic invertebrates (Zhang & Li 2011), the 200 U group was exposed to extremely high sulphide levels when compared to other stocking densities (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, H 2 S was found to cause increased levels of 8-oxo-7,8-dihydro-2′-deoxyguanosine in coelomocytes and in Glycera dibranchiata . 35 In cultured human lung fibroblasts, H 2 S induced a concentration-dependent increase in micronuclei, a finding suggestive of DNA damage. 36 Finally, H 2 S was shown to be weakly mutagenic in the Salmonella typhimurium strain 1535.…”
Section: Introductionmentioning
confidence: 98%
“…The toxic effect of sulfide is well known, inhibiting respiration by acting on cytochrome c oxidase in heterotrophic bacteria (12)(13)(14)(15) and photosynthesis by binding to metalloproteins of photosynthesis system II (PSII) (16)(17)(18)(19). Sulfide can reach high concentrations in specific habitats, such as hydrothermal vents and seeps (10) and coastal mudflats (11). Sulfide is mainly derived from sulfate as the terminal electron acceptor for organic mineralization by sulfur-reducing bacteria in OMZs (10).…”
mentioning
confidence: 99%